Effects of different WAAM current deposition modes on the mechanical properties of AISI H13 tool steel - Hackenhaar, William; Mazzaferro, José A. E.; Mazzaferro, Cintia C. P.; Grossi, Niccolò; Campatelli, Gianni (Welding in the world, 2022)
In this work, AISI H13 tool steel build-ups were produced through wire arc additive manufacturing (WAAM). The cold metal transfer (CMT), low spatter control (LSC) and pulsed synergic (PS) current deposition modes were compared. Similar deposition strategy was employed in order to attempt to evaluate the influence of energy input on geometrical and mechanical properties of the deposits. To evaluate the mechanical properties of the deposits, hardness and tensile tests were carried out. Microstructures were analysed in optical microscope. As a result of the intrinsic characteristics of each current waveform and adjustments of the heat source used to perform the deposits, the heat input value was similar for CMT and PS mode and lower for the LSC mode. The CMT deposit was the tallest and widest. Temperatures were higher using the PS deposition mode. The hardness values for all deposits were higher than the usual ones for this tool steel. The microstructure was composed by hard phases, and the precipitates at grain boundaries were responsible for the brittle fracture observed in tensile specimens.